Prediction of hydraulic conductivity loss from relative water loss: new insights into water storage of tree stems and branches - Rosner, Sabine (2019)
More frequently occurring, drought waves call for a deeper understanding of tree hydraulics and fast and easily applicable methods to measure drought stress. The aim of this study was to establish empirical relationships between the percent loss of hydraulic conductivity (PLC) and the relative water loss (RWL) in woody stem axes with different P50, i.e. the water potential (Ψ) that causes 50% conductivity loss. Branches and saplings of temperate conifer (Picea abies, Larix decidua) and angiosperm species (Acer campestre, Fagus sylvatica, Populus x canescens, Populus tremula, Sorbus torminalis) and trunk wood of mature P. abies trees were analyzed. P50 was calculated from hydraulic measurements following bench top dehydration or air injection. RWL and PLC were fitted by linear, quadratic or cubic equations. Speciesor age-specific RWLs at P50 varied between 10 and 25% and P88, the Ψ that causes 88% conductivity loss, between 18 and 44%. P50 was predicted from the relationship between Ψ and the RWL. The predictive quality for P50 across species was almost 1:1 (r2 =0.99). The approach presented allows thus reliable and fast prediction of PLC from RWL. Branches and saplings with high hydraulic vulnerability tended to have lower RWLs at P50 and at P88. The results are discussed with regard to the different water storage capacities in sapwood and survival strategies under drought stress. Potential applications are screening trees for drought sensitivity and a fast interpretation of diurnal, seasonal or drought induced changes in xylem water content upon their impact on conductivity loss.